2009
DOI: 10.1136/gut.2009.181347
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-derived cell injection to treat anal incontinence due to obstetric trauma: pilot study with 1 year follow-up

Abstract: Injection of autologous myoblasts is safe, well tolerated, and significantly improves symptoms of anal incontinence due to obstetric anal sphincter trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(140 citation statements)
references
References 36 publications
8
132
0
Order By: Relevance
“…3 Urethral sphincter deficiency resulting in incontinence is a condition that is also likely to benefit from this type of therapy. [4][5][6][7][8] Smooth muscle provides an important function for a number of physiological processes. This includes, for example, peristaltic movements within the gastrointestinal tract, 9 regulation of blood pressure, 10 and maintaining ventilation of the airways.…”
Section: Introductionmentioning
confidence: 99%
“…3 Urethral sphincter deficiency resulting in incontinence is a condition that is also likely to benefit from this type of therapy. [4][5][6][7][8] Smooth muscle provides an important function for a number of physiological processes. This includes, for example, peristaltic movements within the gastrointestinal tract, 9 regulation of blood pressure, 10 and maintaining ventilation of the airways.…”
Section: Introductionmentioning
confidence: 99%
“…Frudinger et al treated 10 patients with autologous myogenic stem cells and found a significant improvement in the AI symptoms at 1‐ and 5‐year controls. However, there was no significant change in anal manometry measurements 39, 40. In a small pilot study, where hASCs therapy was used in combination with surgical sphincteroplasty in treatment of AI, there was no difference in AI symptoms between the hASC and saline injection group.…”
Section: Discussionmentioning
confidence: 85%
“…To simplify the cell isolation and proliferation process, Mazzanti et al used freshly isolated minimally manipulated bone‐marrow derived mononuclear cells without expansion and found them to be as effective as in vitro expanded BM‐MSCs in the recovery of iatrogenic anal sphincter rupture 38. Muscle‐derived stem cell injections have been used in small pilot studies in women and the results are promising 39, 40, 41. Frudinger et al treated 10 patients with autologous myogenic stem cells and found a significant improvement in the AI symptoms at 1‐ and 5‐year controls.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show promising results with improvement in FI symptoms and low complication rates. 15 In conclusion, fecal incontinence is an overlooked, underreported debilitating condition; medical practitioners must be comfortable with its evaluation and management. The most important aspect of the initial workup is obtaining a thorough history.…”
Section: Treatment: Nonoperativementioning
confidence: 99%